The Effectiveness of Android-assisted Optical Devices Learning to Improve Students’ Conceptual Understanding - Nanda, Oktama Azarya; Wilujeng, Insih (Department of Science Education, Universitas Sultan Ageng Tirtayasa, 2018)
This research aims to find the effectiveness of Android-assisted optical devices learning to improve students’ conceptual understanding. This research was a quasi-experimental research with a pretest-posttest design. This research involved 60 second year high school students in West Kutai Regency, East Kalimantan. The instrument for the data collection was comprehension questions about conceptual understanding on optical devices tested through pretest and posttest. The conceptual understanding data was analyzed using anava mix design. The result shows that learning optical devices using an android application is more effective in improving students’ conceptual understanding compared to conventional learning which is not using an android application